Conical Biosilicate Implant for Volume Augmentation in Anophthalmic Sockets - Brandão, Simone Milani; Schellini, Rodolfo Artioli [UNESP]; Peitl, Oscar; Zanotto, Edgar Dutra; Matayoshi, Suzana; Meneghim, Roberta Lilian Fernandes de Sousa [UNESP]; Schellini, Silvana Artioli [UNESP] (Wolters Kluwer, 2020)
The ideal implant for anophthalmic socket reconstruction has yet to be developed. Biosilicate, a highly bioactive glass-ceramic, has been used in the composition of conical implants, which were initially tested in rabbit orbits with excellent results. However, the use of this material and the conical shape of the implants require further study in the human anophthalmic socket. Thus, we propose the use of a new conical implant composed of Biosilicate for orbital volume augmentation in anophthalmic sockets. This prospective, randomized study included 45 patients receiving conical implants composed of either Biosilicate or polymethylmethacrylate (control). Patients were evaluated clinically before and 7, 30, 60, 120, and 180 days after implantation. Systemic evaluations, laboratory tests, and computed tomography of the orbits were performed preoperatively and 180 days postoperatively. Both groups had good outcomes with no significant infectious or inflammatory processes. Only 1 patient, in the Biosilicate group, had early implant extrusion. Laboratory tests were normal in both groups. Computed tomography scans showed that the implants in both groups were well positioned. The new conical implant composed of Biosilicate was successfully used for anophthalmic socket reconstruction. This implant may provide a good alternative to the only conical implant currently available on the market, which is composed of porous polyethylene.